The Relationship among Language Mindset, Corrective Feedback Preferences, and Follow-Up Strategies of Students in Writing Scientific Texts - Prihatini, Arti; Pangesti, Fida; Wuryaningrum, Rusdhianti (Universitas Pendidikan Mandalika, 2024)
Student learning success is primarily determined by their skills in writing scientific texts as their final assignment. However, students experience problems when preparing research proposals. The obstacles experienced were triggered by students' views that scientific writing is challenging and students' lack of understanding of input from lecturers. So, this research has four objectives, namely describing (a) language mindset, (b) corrective feedback preferences, (c) students' follow-up strategies in writing scientific texts, and (c) the correlation of the three. This research employed a mixed method. The research subjects were Indonesian Language Education students at the University of Muhammadiyah Malang. Data was collected using questionnaires and in-depth interviews. The results show that the highest average language mindset is a growth language mindset (4.573). As many as 95.3% of students had an average questionnaire of 3.5-5.00, so most students had a growth language mindset tendency. The dominant corrective feedback that students prefer is an explicit correction (4,895). The average of the follow-up strategy is 4.30, demonstrating that students try to receive corrective feedback on their written scientific texts from lecturers. Based on the correlation results, there is a significant relationship between language mindset and corrective feedback preference (0.529); there is a relationship between language mindset and follow-up strategy-based corrective feedback (0.297); but there is no significant relationship between corrective feedback preference and follow-up strategy based corrective feedback (0.160). The conclusion is that scientific text writing guidance activities need to encourage an increase in students' growth language mindset, corrective feedback preferences, and follow-up strategies in writing scientific text.Â